TP038/#1408 Rucaparib maintenance after bevacizumab maintenance following carboplatin based first line chemotherapy in ovarian cancer. (4th December 2022) - Dysarz, Jessica; Braicu, Elena Ioana; Pietzner, Klaus; Zocholl, Dario; Rogmans, Gunther; Wimberger, Pauline; Egger, Eva-Katharina; Gerber, Jens; Eichbaum, Michael; Heitz, Florian; Kupec, Tomás; Koch, Martin; et al.
Abstract : Objectives: Most patients with Ovarian cancer (OC) are diagnosed in advanced stages. In Germany; a current therapy option for advanced BRCAwt OC patients is debulking surgery; followed by platinum based chemotherapy and bevacizumab; followed by maintenance therapy with bev or monotherapy with PARP inhibitors. The anticancer effects of PARPi seem to be increased by the addition of antiangiogenic drugs. Preclinical data showed increased HRD in tumors pretreated with bev; and clinical trials showed a benefit of the combination of antiangiogenic drugs and PARPi vs. PARPi alone. Hence; in this study we will evaluate maintenance after maintenance for the treatment of advanced primary high grade BRCAwt OC. Methods: 190 BRCAwt patients with advanced high grade OC; fallopian tube-; primary peritoneal cancer or clear cell carcinoma will be randomized 2:1 to receive either rucaparib or placebo as maintenance therapy following first line chemotherapy and at least 12 months of bevacizumab. Rucaparib therapy will continue for 24 months, until disease progression or unacceptable toxicity. Randomization is stratified by surgery timepoint (neoadjuvant vs. adjuvant); surgical outcome (no residual tumor vs. residual tumor) and response to chemotherapy/bevacizumab (CR/NED vs. PR/SD). Primary endpoint is PFS per RECIST v1.1. Secondary endpoints are PFS2; quality of life (validated questionnaires); daily activity; time to next medical intervention; time to next subsequent therapy; safety assessments and OS. 35 patients are randomized in the study. Results: Trial in progress: there are no available results at the time of submission. Conclusions: Trial in progress: there are no available conclusions at the time of submission.